Analysis of the influence of clinical and demographic factors on the understanding of cataract informed consent - Barreiro González, Antonio; Rahhal-Ortuño, Miriam; Fernández Santodomingo, Alex S.; Bueso Bordils, Jose I.; Cañada Martínez, Antonio J.; López Prats, María J.; Hurtado Sarrió, Mercedes (Acta Bioethica, 2020)
Purpose: To estimate the influence of clinical and demographical information in the understanding of cataract surgery informed consent, identifying less understandable areas. To assess informed consent document concept. Methods: Multiple-choice questionnaire was designed to collect information and to evaluate the understanding of cataract surgery and informed consent. An ordinary regression model was adjusted to express the effect of clinical and demographic variables to the questionnaire score. Results: The study comprised 180 patients. Sex (female, p=0.404), non-ophthalmologist source of information (p=0.397), previous surgical history (p=0.571), not having a companion (p=0.396) nor the days since the signing of informed consent form (p=0.535) had no influence in the understanding of cataract surgery informed consent. Age (r=-0.083, p<0.001) and educational level (secondary studies r=1.845, p<0.001; tertiary studies r=4.289, p<0.001) showed statistical significance with greater strength of association educational level (OR secondary studies = 6.33, OR tertiary studies = 72.86) than age had (OR = 0.92). Conclusion: Patient’s knowledge about cataract informed consent is influenced by age and educational level. The purpose and the risks, consequences of not performing surgery and postoperative indications are the least understood topics. Informed consent is seen as a forced legal obligation.